A comparison of initial stiffness formulations for small-strain soil–pile dynamic Winkler modelling - Prendergast, L.J.; Gavin, K. (Elsevier, 2016)
Dynamic Soil-Structure Interaction (DSSI) is an area of much ongoing research and has wide and varied applications from seismic response analysis to offshore wind foundation response. DSSI covers a wide range of load regimes from small-strain vibrations to large strain cyclic loading. One of the most common ways to model DSSI uses the Winkler model, which considers the soil as a series of mutually independent springs. The difficulty with modelling DSSI arises with the inelastic and nonlinear load–displacement response of soil with increasing strain, therefore modelling of large-strain DSSI relies on the specification of many interrelated parameters. The relative magnitude of these parameters can have a significant effect on the modelled response. In this paper, the specification of an initial stiffness coefficient to model the elastic (small-strain) response of a soil–pile system is investigated. The coefficient of subgrade reaction method can be used to generate spring stiffness moduli for Winkler type models. A number of subgrade reaction theories have been proposed and their application to the problem of static loading has been widely studied. However, relatively little research concerning the application of these models for small-strain dynamic loading has been undertaken. This paper describes a sensitivity study in which a number of subgrade reaction models were used to estimate the frequency response at smallstrain levels for a range of pile geometries and ground conditions. A field investigation was undertaken on two piles with different slenderness ratios to estimate the frequency response and damping ratios. The experimental results were compared to predictions of damped natural frequency obtained from numerical models using the force input and measured damping ratio from each experiment. The ability of each subgrade reaction formulation to model the response at small-strain levels is evaluated.